At the crossroads: The euro and its central bank guardian (and savior?) - Jörg Bibow (Levy Economics Institute of Bard College, 2012)
This paper investigates the role of the European Central Bank (ECB) in the (mal-) functioning of Europe's Economic and Monetary Union (EMU), focusing on the German intellectual and historical traditions behind the euro policy regime and its central bank guardian. The analysis contrasts Keynes's chartalist conception of money and central banking to the peculiar post-WWII German traditions as nourished by the Bundesbank and based on fear of fiscal dominance. Keynes viewed the central bank as an instrument of the state, leading and controlling the financial system and wider economy but ultimately an integral part of, and controlled by, the state. By contrast, the Maastricht (EMU) regime (of German design) positions the central bank as controlling the state (and disciplining labor unions, too). The paper identifies a number of potential weaknesses that could undermine the euro's guardian of stability, and ultimately the euro itself. Essentially, the national success of the Bundesbank model in pre-EMU times has left Europe stuck with a policy regime that is wholly unsuitable for the area as a whole. As the general perception in Germany today is that the euro crisis has confirmed the soundness of the key stability-oriented principles and ideas behind the euro regime, and of the virtuousness of Germany's own conduct under that regime in particular, it is hard to see how Europe might escape doom through regime reform and policies that would need to permanently put to rest Bundesbank wisdom.
Keywords: B22; E58; E61; E65; 330; central banking; Bundesbank; ordoliberalism; economic and monetary union; euro crisis